(untitled) (Jurnal Bakti Masyarakat Indonesia, 2019)
This paper discusses the implementation of community service to transform lean leadership in small to medium industries. This PKM was carried out by organizing lean manufacturing and coaching clinic training for two days. The next phase of assistance in lean implementation continues to be carried out and evaluated periodically. It is hoped that lean production based management approach can improve the competitiveness of small and medium industries in Indonesia ABSTRAK: Tulisan ini membahas mengenai pelaksanaan kegiatan pengabdian masyarakat untuk mentransformasikan kepemimpinan lean pada industri kecil menengah. Adapun PKM ini dilaksanakan dengan menyelenggarakan pelatihan lean manufacturing dan coaching clinic selama dua hari. Tahap selanjutnya pendampingan dalam implementasi lean terus dilakukan dan dievaluasi secara berkala. Harapannya, pendekatan manajemen berbasis lean production dapat meningkatkan daya saing industri kecil menengah di Indonesia.